Plantas medicinais e fitoterápicos como alternativa terapêutica às infecções urinárias: um diagnóstico dessa realidade na saúde pública de Mossoró - Queiroga, Geruzia Marques Teodoro (Universidade Federal Rural do Semi-Árido, 2015)
Medicinal plants are a therapeutic resource and are being increasingly used at societies worldwide. It constitutes a preservation tool of the cultural environment, of the economic and social development, promoting improvements in the population's quality of life. The aim of this study was to evaluate the use of phytotherapy as a therapeutic alternative in the framework of the public health of Mossoró/RN, considering the popular and scientific knowledge. The data collection instrument regarding the informations about the phytotherapy was the structured questionnaire, administered to a population of 453 subjects, among which, users (269) and SUS s health professionals (184), enrolled in the Basic Health Units. For evaluation of the use of vegetable species, on specific illness, was made the determination of the antibacterial activity of the plants s extracts cited in ITU (Phyllanthus niruri L, Punica granatum L and Zea mays L), against clinical isolates of people from the community and ATCC s standard strains of Escherichia coli, Klebsiella pneumoniae and Staphylococcus aureus, utilizing the disk diffusion in solid medium method. The crude extracts were tested at concentrations of 100, 200 and 300 mg/mL having DMSO as solvent. To the analysis of the data obtained with the questionnaire was used Fisher's exact test for contingency tables, as for the comparison of the diameter of the extracts inhibition halos, was used the variance analysis in the design in randomized blocks, and for the comparison of the halos means the Student-Newman-Keuls test, with the R software with a 5% significance level. The results showed that 86.41% of health professionals and 89.96% of public health services users know, accept and utilize the phytotherapy as a therapeutic option, and the Punica granatum extract as the most effective and with the greater spectrum of action regarding the tested bacterias, confirming the popular knowledge about the antibacterial property of these plants, enabling the implantation of a municipal health public policy, focused on phytotherapy as a way to ensure the right to health of the population, without necessarily depend on allopathy, having the common sense as a search instrument of potentially therapeutic plants in the region
Medicinal plants and phytotherapeutic as therapeutic alternative for the urinary infections: a diagnosis of this reality in Mossoró s public health
Keywords: Medicinal plants; Phytotherapy; Phyllanthus niruri; Punica granatum; Zea mays; Plantas medicinais; Fitoterapia; Phyllanthus niruri; Punica granatum; Zea mays; MULTIDISCIPLINAR::CIENCIAS AMBIENTAIS::AMBIENTE, TECNOLOGIA E SOCIEDADE